Characterisation of the Gaia Red Clump. Issue 67 (17th July 2015) - Ruiz-Dern, L.; Babusiaux, C.; Arenou, F.; Turon, C.
Abstract : Red Clump (RC) stars are known to be good distance indicators. However the accuracy on these calculations strongly depends on the knowledge of their basic properties: a complete calibration is required.